2021
DOI: 10.2147/dmso.s308250
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Metabolic Syndrome and Cognitive Function: A Population-Based Study of Middle-Aged and Elderly Adults in Rural China

Abstract: Introduction To explore the relationship between metabolic syndrome (MetS) and cognitive impairment in a low-income and low-education population. Methods All residents aged ≥45 years in a low-income population in Tianjin, China, were eligible to participate in this study. The Mini-Mental State Examination (MMSE) scale was used to conduct a preliminary screening and assessment of the participants’ cognitive statuses. The MMSE components are orientation, registration, att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“… 9 In addition, there is a correlation between metabolic syndrome and cognitive function. 10 However, these disorders significantly impact the quality of life and public health. Therefore, it is critical to identify MCI early diagnostic biomarkers in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%
“… 9 In addition, there is a correlation between metabolic syndrome and cognitive function. 10 However, these disorders significantly impact the quality of life and public health. Therefore, it is critical to identify MCI early diagnostic biomarkers in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%
“… 18 However, in contrast to the findings of these studies, a recent study that involved participants from Tianjin, China, aged 45 years and older with poor income showed an association between high triglycerides and cognitive decline. 19 The researchers of the Chinese study 19 suggested that the differences between these various studies might be related to the nutritional and metabolic status of the different populations. Other studies that have used triglyceride-glucose index (TyG), an insulin resistance biomarker (calculated from triglyceride values and fasting serum glucose), reported that an increased TyG index is strongly associated with the risk of developing cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…This was a population-based, cross-sectional study conducted from April 2014 to January 2015 in rural areas of Tianjin, China. The participants were from a sub-cohort of the Tianjin Brain Study ( 13 , 14 ), which has been described previously. Briefly, approximately 95% of the individuals in this study reported a 2014 disposable income per capita of <1,600 USD ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…The specific information collected and the associated processes have been described in detail ( 14 ). Using pre-designed questionnaires, uniformly trained investigators collect participants' information through face-to-face interviews.…”
Section: Methodsmentioning
confidence: 99%